TGF-β induces cholesterol accumulation to regulate the secretion of tumor-derived extracellular vesicles - Dorival Mendes Rodrigues-Junior; Chrysoula Tsirigoti; Konstantina Psatha; Dimitris Kletsas; Michalis Aivaliotis; Carl-Henrik Heldin; Aristidis Moustakas (Journal of Experimental & Clinical Cancer Research)
Abstract Background Cancer cells are avid extracellular vesicle (EV) producers. EVs transport transforming growth factor-β (TGF-β), which is commonly activated under late stages of cancer progression. Nevertheless, whether TGF-β signaling coordinates EV biogenesis is a relevant topic that remains minimally explored. Method We sought after specific TGF-β pathway mediators that could regulate EV release. To this end, we used a large number of cancer cell models, coupled to EV cell biological assays, unbiased proteomic and transcriptomic screens, followed by signaling and cancer biology analyses, including drug resistance assays. Results We report that TGF-β, by activating its type I receptor and MEK-ERK1/2 signaling, increased the numbers of EVs released by human cancer cells. Upon examining cholesterol as a mediator of EV biogenesis, we delineated a pathway whereby ERK1/2 acted by phosphorylating sterol regulatory element-binding protein-2 that transcriptionally induced 7-dehydrocholesterol reductase expression, thus raising cholesterol abundance at both cellular and EV levels. Notably, inhibition of MEK or cholesterol synthesis, which impaired TGF-β-induced EV secretion, sensitized cancer cells to chemotherapeutic drugs. Furthermore, proteomic profiling of two distinct EV populations revealed that EVs secreted by TGF-β-stimulated cells were either depleted or enriched for different sets of cargo proteins. Among these, latent-TGF-β1 present in the EVs was not affected by TGF-β signaling, while TGF-β pathway-related molecules (e.g., matrix metalloproteinases, including MMP9) were either uniquely enriched on EVs or strongly enhanced after TGF-β stimulation. EV-associated latent-TGF-β1 activated SMAD signaling, even when EV uptake was blocked by heparin, indicating competent signaling capacity from target cell surface receptors. MMP inhibitor or proteinase treatment blocked EV-mediated SMAD signaling, suggesting that EVs require MMP activity to release the active TGF-β from its latent complex, a function also linked to the EV-mediated transfer of pro-migratory potential and ability of cancer cells to survive in the presence of cytotoxic drugs. Conclusion Hence, we delineated a novel signaling cascade that leads to high rates of EV generation by cancer cells in response to TGF-β, with cholesterol being a key intermediate step in this mechanism. Graphical Abstract • TGF-β increases EV release by activating a MEK-ERK1/2-SREBP2-DHCR7 signaling and transcriptional pathway. • TGF-β-induced DHCR7 expression raises cholesterol abundance that promotes EV release. • EVs carry surface latent TGF-β and MMP9 that can activate TGF-β receptor signaling on the surface of recipient cells.